Stratospheric PULSE–continental cold air outbreak coupling relationships: Interannual and interdecadal changes - Yu, Yueyue; Yu, Xueting; Guan, Zhaoyong; Hu, Dingzhu; Shi, Chunhua; Guo, Dong; Rao, Jian (Frontiers in Earth Science, 2023)
Stratospheric processes and their role in weather and climate have attracted increasing interests. The correspondence between the occurrence of pulse-like stronger stratospheric poleward warm airmass transport (PULSE) events and the continental-scale cold air outbreak (CAO) events in northern hemispheric winter is found not stable from year to year. This increases the difficulties in utilizing the more predictable stratospheric variability in the sub-seasonal forecasts of CAOs, which can cause cold hazards. Using the ERA5 Reanalysis data covering 37 winters (November–March) in the period 1979–2015, this study categorizes the CAO events over mid-latitudes of Eurasia (CAO_EA) and those over North America (CAO_NA) into two groups: coupled and decoupled with the PULSE events. The coupled CAOs are further categorized into events that are respectively lead-coupled and lag-coupled with PULSEs. The intensity and affected area of extremely cold temperatures tend to be larger during CAOs that are coupled with PULSEs, particularly during the CAO_NA events that are lag-coupled with PULSEs and CAO_EA events that are lead-coupled with PULSEs. Remarkable interannual and interdecadal variations are observed in the percentage of CAOs that are coupled with PULSEs for each winter, which is an importance reference for determining the window of opportunity for skillful sub-seasonal forecasts of CAO by using the stratospheric signals. At both interdecadal and interannual timescales, a warm phase of El Niño-Southern Oscillation (ENSO) in winter is favorable for the higher lag-coupling rate of CAO_NA and lead-coupling rate of CAO_EA, and vice versa. The ENSO signals related to the interdecadal changes of CAO coupling rate in winter can be traced back to the previous winter, while an ENSO phase transition from the previous winter to the current winter is closely related to the interannual changes of CAO coupling rate.